2013
DOI: 10.1007/s00404-013-3046-y
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and depression during and after pregnancy in the Franconian Maternal Health Evaluation Studies (FRAMES)

Abstract: Socioeconomic factors define subgroups that have different depression scores during and after pregnancy. Partnership status appears to be one of the most important influencing factors and could be useful for identifying women who should be offered an intervention to prevent possible negative effects on the mother or child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
4
30
0
1
Order By: Relevance
“…Similar to other studies in the literature, lower age (Bottino et al 2012; Räisänen et al 2014; Siegel & Brandon, 2014) and inferior per capita income (Abdollahi et al 2014; Hein et al 2014; Alfayumi-Zeadna et al 2015) were associated with mental disorders in the postpartum period. According to Bottino et al (2012), maternal age was significantly associated with PPD.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to other studies in the literature, lower age (Bottino et al 2012; Räisänen et al 2014; Siegel & Brandon, 2014) and inferior per capita income (Abdollahi et al 2014; Hein et al 2014; Alfayumi-Zeadna et al 2015) were associated with mental disorders in the postpartum period. According to Bottino et al (2012), maternal age was significantly associated with PPD.…”
Section: Discussionsupporting
confidence: 83%
“…20 Similarly, according to study done by Hein et al, parity, and education status, income, and partnership status were found to be predictive factors for depression during pregnancy. 21 Most of the previously established risk factors were identified as predictor of antenatal depression in this study.…”
Section: Correlates Of Depression In Pregnancymentioning
confidence: 68%
“…By contrast, having an unplanned pregnancy and a lack of social support (both real and perceived) are well‐known significant risk factors for the development of PND. The correlation between a lack of partner support and PND is similarly well established . However, there is uncertainty regarding the specific effect of partner support in the setting of an unplanned pregnancy.…”
Section: Discussionmentioning
confidence: 99%